Effect of montelukast in preventing dengue with warning signs among patients with dengue: A multicenter, randomized, double-blind, placebo-controlled trial. - Nattapat Nitinai; Worapong Nasomsong; Worayon Chuerboonchai; Akarawin Tweekittikul; Vutthikorn Khingmontri; Bawornnan Panuvatvanich; Thananut Bangchuad; Maynanchaya Pongpraijaroen; Tanapol Roongfa-Ngarm; Vasin Vasikasin (Public Library of Science (PLoS), 2024)
Background Montelukast has shown potential as a candidate treatment for dengue. This study aimed to evaluate the efficacy and safety of montelukast in preventing dengue with warning signs. Methods This multicenter, randomized, double-blind, placebo-controlled trial enrolled adult participants with NS1 antigenemia in Thailand. The participants were randomly assigned to receive either oral montelukast (10 mg) or a placebo for 10 days or until all symptoms resolved. Results Between January 2021 and June 2023, 358 participants were enrolled and randomly assigned (1:1) to receive either montelukast or placebo. The incidence rate of warning signs in the montelukast group and the placebo group were 9.5% and 7.8% per day, respectively. There was no difference between the two groups (HR 1.36; 95%CI 0.94-1.96, P = 0.105). No statistically significant differences were observed in the incidence rate of severe dengue, hemoconcentration, thrombocytopenia, admission, or recovery from dengue. Neither dengue shock, nor mortality occurred. The montelukast group exhibited a decreased incidence rate of transaminase elevations (0.7% vs 1.4% per day, HR: 0.48, 95%CI 0.25-0.90, P = 0.023). Conclusion Oral montelukast does not reduce the incidence of warning signs among patients with dengue. Nevertheless, the observed decrease in transaminase elevations warrants further investigation to evaluate the potential effect of montelukast. Clinical trials registration Clinicaltrials.gov, NCT04673422, registered on 9 December 2020.